Autoestima y comprensión lectora en estudiantes de primaria de la Institución Educativa N° 60321 San Francisco de Pinsha, rio Napo 2025 - Paredes Chavez, Agapito (2025)
The purpose of this study was to analyze the relationship between self-esteem and reading comprehension levels in elementary school students. A quantitative, non experimental, cross-sectional methodology was applied, with a descriptive correlational approach to analyze the relationships between variables. A census sample of 52 students in grades 1 through 6 was used. Data collection was carried out using structured questionnaires and a reading comprehension test. With a Kendall's Tau-b coefficient of 0.787, the most important results of this study reveal that there is a positive and substantial association between self-esteem and reading comprehension. This correlation was discovered after conducting the research. It follows that an increase in self-esteem is associated with improved performance in text comprehension. Therefore, the study's hypothesis is confirmed, establishing a direct relationship between self-esteem and reading comprehension.